Study of GABA in Healthy Volunteers: Pharmacokinetics and Pharmacodynamics - Li, Junfeng; Zhang, Zhaoyun; Liu, Xiaoxia; Wang, Yi; Mao, Fei; Mao, Junjun; Lu, Xiaolan; Jiang, Dongdong; Wan, Yun; Lv, Jia-Ying; Cao, Guoying; Zhang, Jing; et al. (Frontiers in Pharmacology, 2015)
Preclinical studies show that GABA exerts anti-diabetic effects in rodent models of type 1 diabetes. Because little is known about its absorption and effects in humans, we investigated the pharmacokinetics and pharmacodynamics of GABA in healthy volunteers. Twelve subjects were subjected to an open-labeled, three-period trial involving sequential oral administration of placebo, 2g GABA once, and 2g GABA three times/day for seven days, with a 7-day washout between each period. GABA was rapidly absorbed (Tmax: 0.5 1 h) with the half-life (t1/2) of 5 h. No accumulation was observed after repeated oral GABA administration for 7 days. Remarkably, GABA significantly increased circulating insulin levels in the subjects under either fasting (1.6-fold, single dose; 2.0-fold, repeated dose; p<0.01) or fed conditions (1.4-fold, single dose; 1.6-fold, repeated dose; p<0.01). GABA also increased glucagon levels only under fasting conditions (1.3-fold, single dose, p<0.05; 1.5-fold, repeated dose, p<0.01). However, there were no significant differences in the insulin-to-glucagon ratio and no significant change in glucose levels in these healthy subjects during the study period. Importantly, GABA significantly decreased glycated albumin levels in the repeated dosing period. Subjects with repeated dosing showed an elevated incidence of minor adverse events in comparison to placebo or the single dosing period, most notably transitional discomforts such as dizziness and sore throat. However, there were no serious adverse events observed throughout the study. Our data show that GABA is rapidly absorbed and tolerated in human beings; its endocrine effects, exemplified by increasing islet hormonal secretion, suggest potential therapeutic benefits for diabetes.